El desarrollo del Derecho del Trabajo: carácter transmisible mortis causa de derecho a la remuneración. Comentario a la Casación Nº 2930-2009-Lima - Pacheco Zerga, Luz (Revista de Derecho, 2020)
The current judgment has resolved a factual situation not covered by labor laws based on an extensive and inclusive interpretation of statutes and constitutional principles on labor matters, as well as purposive and unitary legal order. The death of a worker which occurred during the trial of nullity of dismissal was filed with his employer, and did not prevent the option to enforce payment of compensation for unfair dismissal to his successors, based on the impossibility of reinstatement in employment. The criteria for interpretation and arguments raised by the Supreme Court, which upheld the decision of the Superior Court, open new horizons for the law operators to achieve equitable solutions based on justice when fundamental rights in the employment relationship are injured.